SOME TOPOGRAPHICAL AND HISTOARCHITECTURAL STUDY OF PARATHYROID GLAND OF LAYING HENS - S, AL-Samarrae, N.; J. Al-Samarrae, A.; 0., Rabie. , F. (The Iraqi Journal of Veterinary Medicine, 1989)
Grossly, there are bilaterally paired, round to oval parathyroid glands in laying hens. The glands are situated, intrathoracic, near the caudal pole of thyroid gland or beneath the division of brachiocephalic arteries. They recieve blood by short branches from common carotid or from oesophageal artery. Histologically, the glands were composed of distinct nests or cords of chief cells but there were no oxyphils as in the parathroid of some mammals.